The need for roots : prelude to a declaration of obligations towards the human being - Weil, Simone, 1909-1943 (Penguin classics., 2023)
"One of the foremost French philosophers of the last century, Simone Weil has been described by André Gide as "the patron saint of all outsiders" and by Albert Camus as "the only great spirit of our time." In this, her most famous work, she diagnoses the malaise at the heart of modern life: uprootedness, from the past and from community. Written towards the end of World War II for the Free French Army, Weil's work is an indispensable and perpetually intriguing text for readers and students of philosophy everywhere. The book discusses the political, cultural and spiritual currents that ought to be nurtured so that people have access to sources of energy which will help them lead fulfilling, joyful and morally good lives" --